Lifestyle of University Students in the Czech Republic - Ludmila Miklánková; Zdeněk Rechtik (University of Zadar, 2022)
Data from various national and international surveys show that people in developed countries do not perform enough physical activity, even though it is an essential part of a healthy lifestyle. University students tend spending their free time inactively by watching TV, using IT-tools, including computer games (e-sports), etc. This research was part of the international project called: Research network for cooperation in the field of sports, recreation and health promotion (ID: EFOP-3.6.2-16-2017-00003). The project was aimed on leisure activities, lifestyle and sports habits of young people. The aim of research was exploration of some aspects of the lifestyle of students in study programs focused on teaching primary and pre-primary aged children. The research group consisted of 503 respondents. The research results indicate that Czech university students have relatively a lot of free time, which a huge part is spend inactively by watching TV or using the Internet on different devices. The main motivation for participating in sports are friends and the basis students received mostly in their families or from their friends. The research revealed some barriers for doing sports. Therefore, our recommendation is to focus on reducing the  barriers that students' experience that may impact their participation on physical activity and give them a huge spectrum of opportunities and options how and where to provide sport activities, because the knowledge about healthy behavior and lifestyle is pretty solid, unlike in other researched countries.